1993
DOI: 10.1111/j.1528-1157.1993.tb02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Secondary Epileptogenesis in Amygdaloid Overkindled Cats: Electroclinical Documentation of Spontaneous Seizures

Abstract: Twenty-four spontaneously occurring convulsive seizures were documented by closed-circuit TV (CCTV)-EEG monitoring in 3 cats subjected to unilateral amygdaloid overkindling for < or = 2 years. Electroclinical manifestations suggested that the seizures originated in the kindled amygdala (AM) (10 seizures in 3 cats), contralateral AM (7 seizures in 3 cats), or ipsilateral frontal cortex (7 seizures in 1 cat). All seizures of AM origin except one occurred during sleep 23 h to 20 days after the last stimulation-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…19,20 Experimental studies support the hypothesis that reiteration of ictal activity may promote the formation of new recurrent excitatory circuits through phenomena of axonal sprouting and synaptic reorganization. 12,16,30 Our findings strengthen these hypotheses.…”
Section: Neurosurg Focus / Volume 21 / July 2006supporting
confidence: 92%
“…19,20 Experimental studies support the hypothesis that reiteration of ictal activity may promote the formation of new recurrent excitatory circuits through phenomena of axonal sprouting and synaptic reorganization. 12,16,30 Our findings strengthen these hypotheses.…”
Section: Neurosurg Focus / Volume 21 / July 2006supporting
confidence: 92%
“…Progressive epileptogenic changes can be examined in the animal model with a variety of techniques (3 1-34). Some observations in the kindling model demonstrated that a form of secondary epileptogenesis can occur in an experimental setting (34,35). Morrell approached this secondary epileptogenesis with studies in humans (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary epileptogenesis has been mentioned in animal experiments and humans [19][20][21] . In many animal studies, some interval after kindling the primary focus, a second epileptogenic lesion occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, proving the presence of this kind of secondary epileptogenesis is very difficult in humans. Previous reports have stated that removal of the primary focus can lead to freedom from seizure [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%